Complications of Rhinoplasty in Patients: An Epidemiological Study - Kazemy, Shahrooz; Najari, Fares; Khalilzadeh, Marzieh; Safavi, Hamideh; Najari, Dorsa (International Journal of Medical Toxicology and Forensic Medicine, 2018)
Background: In addition to odor perception, the nose also plays an important role in breathing and speech. In Iran, 70% of plastic surgeries is performed on the nose. Methods: In the present study, all patients underwent rhinoplasty during 5 years from April 2012 to March 2017 and were evaluated using a census method. A researcher-made questionnaire including the following variables were used: age, gender, level of education, season of performing the operation, length of hospitalization, occupational status, type of surgery, surgical procedure, and type of repair surgery. The obtained data were analyzed by SPSS. Results: A total of 106 individuals, with the mean age of 27.37 years were enrolled into the study. Most of the rhinoplasty surgeries were performed in summer and the lowest frequency was in spring. Most clients had a diploma, and in terms of occupational status, most subjects were students. Conclusion: There was a significant relationship between gender, educational level, and type of surgery.